Suppression of amplitude modulation induced by polarization mode dispersion using a multi-degree-of-freedom fiber filter. (23rd October 2018) - Li, Rao; Jiang, Youen; Qiao, Zhi; Huang, Canhong; Fan, Wei; Li, Xuechun; Lin, Zunqi
Abstract : Polarization mode dispersion (PMD) in fibers for high-power lasers can induce significant frequency modulation to amplitude modulation (FM-to-AM) conversion. However, existing techniques are not sufficiently flexible to achieve efficient compensation for such FM-to-AM conversion. By analyzing the nonuniform transmission spectrum caused by PMD, we found that the large-scale envelope of the transmission spectrum has more serious impacts on the amount of AM. In order to suppress the PMD-induced FM-to-AM conversion, we propose a novel tunable spectral filter with multiple degrees of freedom based on a half-wave plate, a nematic liquid crystal, and an axis-rotated polarization-maintaining fiber. Peak wavelength, free spectral range (FSR), and modulation depth of the filter are decoupled and can be controlled independently, which is verified through both simulations and experiments. The filter is utilized to compensate for the PMD-induced FM-to-AM conversion in the front end of a high-power laser facility. The results indicate that, for a pulse with phase-modulation frequency of 22.82 GHz, the FM-to-AM conversion could be reduced from 18% to 3.2% within a short time and maintained below 6.5% for 3 h. The proposed filter is also promising for other applications that require flexible spectral control such as high-speed channel selection in optical communication networks.